Anthropocene, Capitalocene and Liberal Cosmopolitan IR: A Response to Burke et al.'s 'Planet Politics'. (January 2018) - Chandler, David; Cudworth, Erika; Hobden, Stephen
This article is a collective response to 'Planet Politics' by Anthony Burke et al., which was published in this journal in 2016, and billed as a 'Manifesto from the End of IR'. We dispute this claim on the basis that rather than breaking from the discipline, the Manifesto provides a problematic global governance agenda which is dangerously authoritarian and deeply depoliticising. We substantiate this analysis in the claim that Burke et al. reproduce an already failed and discredited liberal cosmopolitan framework through the advocacy of managerialism rather than transformation; the top-down coercive approach of international law; and use of abstract modernist political categories. In the closing sections of the article, we discuss the possibility of different approaches, which, taking the Anthropocene as both an epistemological and ontological break with modernist assumptions, could take us beyond IR's disciplinary confines.